Threat of emigration for the socio-economic development of Lithuania - Rakauskienė, Ona Gražina; Ranceva, Olga (Business, Management and Economics Engineering, 2013)
The phenomenon of international migration is among the most prominent global demographic processes currently taking place and influencing both the economic and social situation worldwide. An intensive emigration is a matter of serious concern for such a small country as Lithuania. Firstly, emigration further exacerbates the current negative demographic indicators (low birth rate, high mortality rate, stagnant average lifespan), which, on the whole, leads to a decrease in the absolute number of the population. Secondly, emigration of persons of working age, leaving behind the population that lacks the capacity for work, reduces the state budget and social security budget revenues. Thirdly, departure of well-educated and competent citizens from the country results in the shrinking of the country’s intellectual potential and diminishing of possibilities of mastering and development of high technologies, innovations and modernisation of the economy. The authors of the article point out the threat posed by emigration to Lithuania’s socioeconomic development and present a comprehensive analysis of the demographic structure of the population: by sex and age, the population ageing tendency, the causes and consequences of emigration. The goal of the article is to raise the issue of emigration from Lithuania and to manifest its impact on the socio-economic development of the country. The object of the article is the extent, dynamics, structure, causes and economic effects of emigration and the problems arising for the economy in the context of emigration.